Preparo e caracterização de compósitos polímero/cerâmica com potencial aplicação como sensor multifuncional - Macario, Leilane Roberta [UNESP] (2013)
This research aimed the preparation and study of polymer/ceramic composites with potential applications as multifunctional sensors, to be used for converting mechanical into electrical energy as well as for light emissions. Different perovskite ceramics powders (pure and doped with europium) were obtained by the Polymeric Precursor Method in order to establish the optimization of piezoelectric and luminescent properties. The composite films were formed by the junction of ceramic powders with poly vinylidene fluoride polymer. The results obtained in this study were divided into three topics. In the first topic ceramic materials BaZrxTi1-xO3 (x = 0, 0.05, 0.08, 0.1, 0.25, 0.50, 0.75 and 1) were obtained and characterized. In the second topic were collated and analyzed the ceramic samples doped with ions Eu3+: Ba1-yEuyZr0,08Ti0,92O3, Ba1-yEuyTiO3, and Ba1- yEuyZrO3 with (y = 0.005, 0.01, 0.02, and 0.04). In the third topic several variables were tested in order to optimize the composites formation using the best conditions. The composites that were obtained in the optimized conditions were analyzed. For structural characterization were used the X-Ray Diffraction and Raman Spectroscopy techniques. The optical property was analyzed by Reflectance Spectroscopy in the UV-Vis range and Photoluminescence measurements. The ceramic surface morphology and the ceramic distribution in the polymer were studied by Scanning Electron Microscopy Field Emission Gun. The electrical conductivity, the longitudinal piezoelectric coefficient d33, and hysteresis curves of these materials were the tools used to analyze their electrical properties. All composites showed the piezoelectricity and the photoluminescence properties and therefore are able to be applied as a multifunctional sensor.